OP0073 RNA-SEQ Based Identification of Factors Involved in Knee Joint Regeneration after Induced Osteoarthritis in Notophthalmus Viridescens. (15th July 2016) - Schoenfeld, C.; Geyer, M.; Schreiyaeck, C.; Junker, S.; Lange, U.; Looso, M.; Braun, T.; Neumann, E.; Mueller-Ladner, U.
Abstract : Background: While tissue damage in mammals is mostly accompanied by fibrotic scar formation, many urodele amphibians including the red-spotted newt Notophthalmus viridescens are able to restore damaged organs or even lost appendages. To study endogenous knee joint regeneration in adult vertebrates, the newt has been established as a model organism in our working group. Like in murine models, osteoarthritis (OA) like symptoms can either be induced by surgical damage to articular cartilage or by intra-articular injection of enzymes, e.g. collagenase. In contrast to murine OA models, newts display symptoms including joint instability and luxation, but joint function is restored in these animals within 3 months. Objectives: To evaluate the molecular pathways involved in knee joint regeneration. Methods: To induce OA, animals were either treated by intra-articular injection of collagenase, mono-iodoacetate or by surgical manipulation of articular cartilage. To study gene expression changes on the transcriptional level during regeneration in the newt, RNA from knee joints was isolated and pooled. Subsequently, a quantitative transcriptome analysis using Illumina® next-generation sequencing (NGS) was performed. Relevant molecular pathways guiding regeneration were analyzed in all OA models tested. Candidate genes using public available databases have been selected, and pathway analyses of the gained data have been performed. Verification of selected candidate genes on the mRNA level has been done by Real Time PCR analyses. Adhesion of newt-derived cell lines and primary newt cells to Tenascin-C (TN-C) was analyzed in vitro . To compare molecular pathways guiding wound healing in amphibians and mice, the expression pattern of selected candidate genes (TN-C and cysteine-rich protein 61 (Cyr61/CCN1)) was also analyzed in murine OA models on the mRNA (Real Time PCR) and protein level (immunohistochemistry). Results: During regeneration, several matricellular proteins including TN-C, CCN family members and their related pathways were found to be differentially regulated. In contrast to the murine OA models, Cyr61/CCN1 mRNA expression levels peaked at day 5 (5.9±0.72 in the collagenase model) and ceased afterwards, while mRNA expression levels in collagenase (day 10 0.6±0.07 to 2.5±0.61 at day 60) and surgically treated newts (day 10 3.39±0.64 to 1.6±0.2 at day 60) showed higher expression levels during later time points. On the protein level, CCN1 expression was detectable in chondrocytes and osteophytes in the collagenase induced murine OA model. In adhesion experiments using the newt-derived cell line B1H1 TN-C coating had anti-adhesive properties (TN-C vs. Control 42% reduction). Conclusions: Extracellular matrix proteins are important during regenerative and repair processes, since they may alter cellular adhesion and guide migration. Identification of novel proteins and evaluation of their impact on cellular behaviour can help to understand the pathways involved. Future experiments on cells from OA patients might help in the development of new treatment options for human OA. Disclosure of Interest: None declared